PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KABUPATEN TORAJA UTARA BERBASIS GREEN TOURISM - Budiandriani, Elsap Patta Pasulu,; Budiandriani, Budiandriani; Suriyanti, Suriyanti; nurnajamuddin, Mahmud (ITB AAS Indonesia Surakarta, 2024)
Sustainable tourism management in North Toraja Regency based on Green tourism has become a priority to support inclusive local economic growth and maintain environmental and cultural sustainability. This study explores how sustainable tourism practices affect local income, job creation, and economic collaboration in North Toraja. Using qualitative and quantitative approaches, this study collected data from stakeholders such as government officials, tourism business actors, and tourists to understand the impact of sustainable tourism management. The results of the study indicate that sustainable tourism is able to increase local income through increased tourist spending in various tourism sectors. In addition, sustainable tourism also contributes to job creation and strengthens local economic cooperation. However, there are challenges that need to be addressed, such as infrastructure capacity and waste management. This study proposes steps to overcome these challenges and strengthen sustainable tourism in North Toraja to ensure sustainable and inclusive economic growth.